Optimasi proses pembuatan kombucha jahe (Zingiber officinale Rosc,) menggunakan metode respon permukaan - Nara Belva Fedora; Rahmah Utami Budiandari (Composite : Jurnal Ilmu Pertanian, 2025)
Ginger (Zingiber officinale Rosc.) can be optimized as a raw material for making kombucha because it contains many active compounds that are beneficial for health. Making kombucha is done with the help of Scoby which requires sugar media as a growth substrate. This study aims to determine the optimal conditions for making ginger kombucha. This study uses the surface response method with central composite design (CCD), the observed variables are sugar concentration and ginger concentration, with a total acid response. The results of the study on the optimum proportion have a desirability value of 0.845 at a sugar concentration of 10% and a ginger concentration of 75% with a total acid response of 0.582±0.012%. From the results of the optimum proportion, characterization was also carried out on antioxidant activity of 182.71 mg TE, vitamin C content of 0.02%, total sugar 0.76%, color, Total Dissolved Solids, pH, and organoleptic tests.